Indices to debates of the House of Assembly - South African Parliament (Cape Town, 1970)
South Africa Parliament House of Assembly. Debates of the House of Assembly (Hansard)
Merged with: Debates of the House of Delegates, and; Debates of the House of Representatives, to form: Debates of Parliament. Debates of Standing Committees. 139 v. 22 cm.
Keywords: Indices to debates; First Session Fourth Parliament; vol. 31; 1970; July; October; House of Assembly; Hansard; Debates; JC045219; Index to speeches